Biomaterial scaffold stiffness influences the foreign body reaction, tissue stiffness, angiogenesis and neuroregeneration in spinal cord injury - Zheng, Yifeng; Nützl, Maximilian; Schackel, Thomas; Chen, Jing; Weidner, Norbert; Müller, Rainer; Puttagunta, Radhika (Bioactive materials, 2025)
Biomaterial scaffold engineering presents great potential in promoting axonal regrowth after spinal cord injury (SCI), yet persistent challenges remain, including the surrounding host foreign body reaction and improper host-implant integration. Recent advances in mechanobiology spark interest in optimizing the mechanical properties of biomaterial scaffolds to alleviate the foreign body reaction and facilitate seamless integration. The impact of scaffold stiffness on injured spinal cords has not been thoroughly investigated. Herein, we introduce stiffness-varied alginate anisotropic capillary hydrogel scaffolds implanted into adult rat C5 spinal cords post-lateral hemisection. Four weeks post-implantation, scaffolds with a stiffness approaching that of the spinal cord effectively minimize the host foreign body reaction via yes-associated protein (YAP) nuclear translocation. Concurrently, the softest scaffolds maximize cell infiltration and angiogenesis, fostering significant axonal regrowth but limiting the rostral-caudal linear growth. Furthermore, as measured by atomic force microscopy (AFM), the surrounding spinal cord softens when in contact with the stiffest scaffold while maintaining a physiological level in contact with the softest one. In conclusion, our findings underscore the pivotal role of stiffness in scaffold engineering for SCI in vivo, paving the way for the optimal development of efficacious biomaterial scaffolds for tissue engineering in the central nervous system.
Online verfügbar: 12. Dezember 2024
Gesehen am 13.03.2025